ANALISIS KOMPARATIF RETURN ON ASSETS (ROA) DAN ECONOMIC VALUE ADDED (EVA) DALAM MENGUKUR KINERJA KEUANGAN BANK BUMN DI BURSA EFEK INDONESIA - Herman Paleni; Iin Dartika (Jurnal Media Ekonomi (JURMEK), 2016)
This research was conducted under the title of Comparative Analysis of Return On Assets (ROA) and Economic Value Added (EVA) in Measuring the Financial Performance of BUMN Banks in the Indonesia Stock Exchange. In measuring the financial performance of state-owned banks on the Indonesia Stock Exchange, conducted using Return On Assets (ROA) and Economic Value Added (EVA), all data used in this study are secondary data, measurement of financial performance of state-owned banks on the Indonesia Stock Exchange during the year 2009-2013 by using Economic Value Added (EVA) shows that BUMN banks are positive or in good condition (EVA> 0) so that they can create added value for the company. Based on the Independent Sample T-Test statistical test shows that there is no significant difference between the calculation of Return on Assets (ROA) and Economic Value Added (EVA) in measuring the financial performance of state-owned banks on the Indonesia Stock Exchange. This is evidenced by the value of profitability (sig)> 0.05 and probability> 0.05 / 2 (two-sided test).